Educatives actions in praxis of the care in cardiovasculares disease: a experience report - Márcia Gabriela Rodrigues de Lima; Elisabeta Albertina Nietsche; Janilene Camara Botega; Cristiane Apio Motta; Glaucia Dal Omo Nicola; Larice Gonçalves Terra; Claudiane Botolli (Universidade Federal de Santa Maria, 2012)
Objective: to describe the activities of promotion, prevention, recovery and treatment of cardiovascular diseases developed in care practice, together with the users with heart disease or patients with a risk factor for the disease. Method: it is an experience report developedin Hemodynamic Laboratory, Intensive Care Unit Cardiology and Family Health Strategy in September from 2009 to July 2010, during the period of supervised trainee in Undergraduate Nursing Courses. The actions compacted in practices of health education in hospital and community spheres. Results: the educational activities were developed in the admission of the user to the service, in group technics and domiciliary visits in order to that they co-responsibilities for its promotion of health, prevention, treatment and recovery of cardiovascular diseases. Conclusion: contrast the need to usehealth education actions in care practices as an element of emancipative users in their self-care